Factors Associated with Skeletal Maturation at the Growth Spurt Period Using a Cervical Vertebrae Maturation Stage: Study of Orthodontic Patients Aged 9-11 Years at RSGM-P FKG USAKTI - Ailsa Fadhilah Putridwita; Olivia Piona Sahelangi (Journal of Indonesian Dental Association, 2023)
Introduction: The growth spurt period is the right time to optimize various aspects of orthodontic treatment. The period of growth spurt in a person can be assessed through biological age which can be determined based on skeletal maturation. Skeletal maturation can be determined by assessing the development of the cervical vertebrae on the lateral cephalogram, namely by using the Cervical Vertebrae Maturation Stage (CVMS) based on the Baccetti method. This simple and widely used method is inserted into the first to sixth stages of the cervical. This method focuses on the second, third, and fourth cervical vertebrae. Objective: To determine the factors associated with skeletal maturation in orthodontic patients aged 9-11 years at RSGM-P FKG USAKTI using the Cervical Vertebrae Maturation Stage (CVMS). Methods: This analytic observational study was conducted by tracing 96 lateral cephalograms of patients aged 9-11 years at RSGM-P FKG USAKTI to determine skeletal maturation using the Cervical Vertebrae Maturation Stage (CVMS) based on the Baccetti method. Chi-Square test is used to determine the relationship between the level of skeletal maturation with gender and age. Results: The majority of skeletal maturation levels in patients aged 9-11 years were in the second cervical stage, 36 patients (37.5%), with female patients in the second cervical stage, 20 samples (41.7%) and the majority of male patients occurred in the first cervical stage with a total of 17 samples (35.4%). In this study there was no relationship between gender and the level of skeletal maturation (p>0.05), but there was a relationship between age and the level of skeletal maturation (p<.05). Conclusion: This study concluded that age is a factor that can be related to the level of skeletal maturation (p<0.05).